Family Friendly Work Practices in the U.S. Revisited - Maniam, Balasundram; Leavell, Hadley; Pustejovsky, Stephanie (International Journal of Economics and Financial Issues, 2016)
The dynamic of the American family is changing at a rapid pace. Households are comprised of dual income families, single mother families, or unmarried couples. These changes call for new approaches to business and how they view family friendly policies. This study looks at the change in family dynamic and how it has led to more family friendly work practices (FFWP). The first part of the study will focus on the four most researched FFWP which are on-site child care, telecommuting, flexible scheduling, and paid family leave. The study will review the advantages and disadvantages associated with FFWP for the company, its employees and its shareholders. Finally, the study will conclude with possible solutions to improve and extend FFWP to more firms in America. Keywords: Family Friendly-Work Practices; FFWP; Advantages & Disadvantages of FFWP; Improvement Solution to FFWP. JEL Classifications: M540, J540